16de- en 17de-eeuwse topografische voorstellingen en het standpunt van de kunstenaar (Bulletin KNOB, 1989)
The 15th century way of rendering buildings and towns as background on altarpieces and illustrations has been developed to an independent genre during the 16th and 17th centuries. During the 18th century topographical representations are produced on a large scale. Here the term topographical representation is treated as the rendering of the outer features of a confined area in drawings or paintings excluding maps and plans because these reproduce reality in abstract form.The topographical image reproduces reality in a recognizable way. Often architecture as specific element makes it possible to identify the representation. Sometimes however the elements are worked up in such a manner that the total picture does not render reality anymore. The choice of a point of view with regard to his subject formed one of the artist's problems.The authors distinguish three sorts of topographical representations: the portrait of a single building or an ensemble, spaces totally surrounded by architecture like streets, canals and squares and the overall view of a town or village. Portraying one building or ensemble, the distance, horizontal and vertical optic angle determine the point of view.Streets and canals mostly are rendered over the longitudinal axis or by choosing an angle of axe and plane which is smaller than 90°. Most representations of squares are U-shaped showing three sides as seen from a standpoint higher than eye-level. The third category gives an overall view of the town. To be able to see the total town's profile the artist had to take a large distance. Panoramas and bird's-eye views both render an area from a place higher than the area itself, the panorama composed after reality and the bird's-eye view fictitiously constructed in the artist's studio.Most I6th and 17th century profiles have been composed in the studio after making several studies on the spot. Joining these studies the construction of the perspective and placing of the high buildings were problematic. Between 1550 and 1650 also many bird's-eye plans have been produced. Resembling the panorama this sort of plan however does not represent the town from one vanishing point.Opposed to the bird's-eye view this type renders every building and therefore gives more information. Thus at each category the same factors distance, horizontal and vertical optic angle play a role at choosing a standpoint Sometimes the artist's meaning to render his subject faithful to reality clashed with his intention to represent it recognizable. Sometimes aesthetic factors like the striving after a better composition prevail over reality. Also the representation of certain events can damage the topographical context.